2014
DOI: 10.1002/poc.3314
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecularcharge transfer in donor‐bridge‐acceptor compounds with paired linearly conjugated or cross‐conjugated pathways

Abstract: An understanding of intramolecular charge transfer in 2-D linearly conjugated and cross-conjugated compounds is necessary for the rational design of molecular electronics, improved solar energy devices, semi-conducting polymers, and materials with nonlinear optical properties. In this work, the femtosecond transient absorption spectra and kinetics of several donor-bridgeacceptor compounds containing cross-conjugated or linearly conjugated bridging groups were obtained. The veratrole group was used as the donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Since Lippert and coworkers reported the dual fluorescence in 4-N,N-dimethylaminobenzonitrile for the first time in 1962, an effect that was ascribed to excited-state intramolecular charge transfer (ICT) from the dimethylamine to the cyano group through the πelectron bridge, much work has been conducted on DBA systems [3] and many DBA materials have been designed for π-conjugated semiconductors. [4] Meanwhile, the influence of different donors, acceptors, [5] π-bridges [6] and ICT working mechanisms [7] has been broadly studied. In 2012, Adachi's group found that donor-acceptor molecules play a crucial role in thermally activated delayed fluorescence, leading to almost 100 % internal quantum efficiency in organic light-emitting diodes, [8] which is one of the most successful applications of DBA materials in organic optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Lippert and coworkers reported the dual fluorescence in 4-N,N-dimethylaminobenzonitrile for the first time in 1962, an effect that was ascribed to excited-state intramolecular charge transfer (ICT) from the dimethylamine to the cyano group through the πelectron bridge, much work has been conducted on DBA systems [3] and many DBA materials have been designed for π-conjugated semiconductors. [4] Meanwhile, the influence of different donors, acceptors, [5] π-bridges [6] and ICT working mechanisms [7] has been broadly studied. In 2012, Adachi's group found that donor-acceptor molecules play a crucial role in thermally activated delayed fluorescence, leading to almost 100 % internal quantum efficiency in organic light-emitting diodes, [8] which is one of the most successful applications of DBA materials in organic optoelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…The design of donor‐bridge‐acceptor (DBA) materials for organic electronics requires fundamental understanding of the DBA system. Since Lippert and coworkers reported the dual fluorescence in 4‐N,N‐dimethylaminobenzonitrile for the first time in 1962, an effect that was ascribed to excited‐state intramolecular charge transfer (ICT) from the dimethylamine to the cyano group through the π‐electron bridge, much work has been conducted on DBA systems [3] and many DBA materials have been designed for π‐conjugated semiconductors [4] . Meanwhile, the influence of different donors, acceptors, [5] π‐bridges [6] and ICT working mechanisms [7] has been broadly studied.…”
Section: Introductionmentioning
confidence: 99%
“…They are, however, useful molecules as well, with potential as the organic component for electronic, optical, and nonlinear optical applications. A specific subcategory of conjugated macrocycles are the [ n ]­radialenes, which are cyclic, carbon-rich molecules with a general formula C 2 n H 2 n that contain n ring atoms and n exocyclic double bonds ( 1 , Figure ). “Expanded radialenes” are derivatives of radialenes that originate by formal insertion of an unsaturated spacer between each pair of exomethylene fragments of a radialene, giving rise to macrocycles such as 2 and 3 (Figure ). Work with expanded radialenes was pioneered by Diederich and co-workers via the introduction of diacetylene moieties into the radialene framework to give derivatives with the general structure 3 , as well as structurally related radiannulenes. More recently, expanded radialenes 2 composed of repeating enyne units have been realized and studied. …”
Section: Introductionmentioning
confidence: 99%
“…9 Such molecules with intramolecular charge transfer bear excellent photophysical properties such as fluorescence. 13 The current computational study deals with the donor-acceptor compounds of two types: (1) coordination complexes of heavier main-group metals and (2) benzanthrone dyes with intramolecular donor-acceptor interactions.…”
Section: Introductionmentioning
confidence: 99%
“…13: Metal-carbon distances in pCp-gallium complexes. In pCp1 Ga , the M-C bond distances are shown for two top of the cavity carbon atoms of each of the three arene rings.…”
mentioning
confidence: 99%